The Comparison of Physician to Computer Interpreted Electrocardiograms on ST-elevation Myocardial Infarction Door-to-balloon Times. Issue 1 (March 2016) - Mawri, Sagger; Michaels, Alexander; Gibbs, Joseph; Shah, Sunay; Rao, Sunil; Kugelmass, Aaron; Lingam, Natesh; Arida, Muhammad; Jacobsen, Gordon; Rowlandson, Ian; Iyer, Karthik; Khandelwal, Akshay; et al.
Abstract : Objective: The purpose of the project was to study the impact that immediate physician electrocardiogram (ECG) interpretation would have on door-to-balloon times in ST-elevation myocardial infarction (STEMI) as compared with computer-interpreted ECGs. Methods: This was a retrospective cohort study of 340 consecutive patients from September 2003 to December 2009 with STEMI who underwent emergent cardiac catheterization and percutaneous coronary intervention. Patients were stratified into 2 groups based on the computer-interpreted ECG interpretation: those with acute myocardial infarction identified by the computer interpretation and those not identified as acute myocardial infarction. Patients (n = 173) from September 2003 to June 2006 had their initial ECG reviewed by the triage nurse, while patients from July 2006 to December 2009 (n = 167) had their ECG reviewed by the emergency department physician within 10 minutes. Times for catheterization laboratory activation and percutaneous coronary intervention were recorded in all patients. Results: Of the 340 patients with confirmed STEMI, 102 (30%) patients were not identified by computer interpretation. Comparing the prior protocol of computer ECG to physician interpretation, the latter resulted in significant improvements in median catheterization laboratory activation time {19 minutes [interquartile range (IQR): 10–37] vs. 16 minutes [IQR: 8-29]; P < 0.029} and in median door-to-balloon time [113 minutes (IQR: 86–143) vs. 85 minutes (IQR: 62–106); P < 0.001]. Conclusion: The computer-interpreted ECG failed to identify a significant number of patients with STEMI. The immediate review of ECGs by an emergency physician led to faster activation of the catheterization laboratory, and door-to-balloon times in patients with STEMI.